Cervical Precancers Originate From Infected Proliferating Reserve Cells: A Comparative Histologic and Genetic Study of Thin and Thick High-grade Squamous Intraepithelial Lesions. (6th April 2022) - Regauer, Sigrid; Reich, Olaf; Kashofer, Karl
Abstract : Human papillomavirus (HPV)-induced invasive cervical squamous cell cancer (SCC) develop via high-grade squamous intraepithelial lesion (HSIL). In contrast to classic thick HSIL, thin HSIL (≤9 cell layers) are poorly documented. This study compares histology, HPV genotypes, and aberrations in 50 cancer genes of 45 thin HSIL to 45 thick HSIL, 20 pT1a SCC, and 40 ≥pT1b SCC. Thin HSIL arose from proliferating reserve cells within endocervical epithelium or immature metaplasia throughout the transformation zone after infection with high-risk HPV genotypes (36/45; 80%), and 20% non–high-risk HPV genotypes compared with 2.5% thick HSIL, pT1a SCC, and ≥pT1b SCC. Thin HSIL were multifocal proliferations with varying epithelial thickness between 1 and 2 to 9 cell layers, with occasional transitions to thick HSIL or concomitant lesions of thick HSIL. Overall, 40% thin HSIL were located distant to and most thick HSIL occurred near or at the squamocolumnar junction. Only 20% thick HSIL showed koilocytosis. All HSIL lacked somatic gene mutations, compared with 30% pT1a and 55%≥pT1b SCC. Overrepresented rare germline variants in the MET, JAK3, and FGFR3 genes occurred in all patient groups. In summary, thin and thick HSIL arose independently of somatic gene mutations. The maturation level of the squamous epithelium at the time of transforming infection determines if a thick HSIL develops directly from HPV-infected proliferating reserve cells via thin HSIL or in stratified glycogenated squamous epithelium via low-grade squamous intraepithelial lesion. These observations raise doubts about the biological relevance of separation into thin and thick HSIL. The oncogenic potential of HPV genotypes but also germline variants may influence the natural history.